Manajemen Isu Penetapan Kuota Haji Tambahan oleh Kementerian Agama dalam Penyelenggaraan Haji Tahun 1445 H/ 2024 M - Yulianto, Dhamar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Research on the issue management of the determination of additional hajj quotas by the Ministry of Religion in the Implementation of the Hajj in 1445 H/2024 M is an interesting topic. Based on the results of searching for articles published in 2014-2024 with the keywords